Dust Storm - Farm Security Administration:::Creator::::::::::::
A dust storm during The 1930's Dust Bowl. Boise City, on the western edge of Oklahoma, was created in 1908 through developers' fraudulent advertisements. It's approximately 350 residents were severely affected by the dust bowl storms. See also numbers 1-214 and 1-215.